Older adults' attitudes toward depression screening in primary care settings and exploring a brief educational pamphlet. (21st April 2017) - Shah, Avani; Scogin, Forrest; Pierpaoli, Christina M.; Shah, Amit
Abstract : Objectives: This study aimed to assess older adults' (OAs') attitudes toward depression screening in primary care settings with a survey and explore the impact of an educational pamphlet on these attitudes. Methods: Older adults above age 55 ( N = 140) were randomly stratified by sex to an intervention or control group. The study included a baseline assessment, posttest, the Geriatric Depression Scale‐Short Form, a two‐page pamphlet on health and mood, and a 10‐question quiz. Results: On the basis of survey responses, most participants (93.6%) were willing to complete a depression screen at their doctor's office, and 92.1% perceived depression screening as valuable to their health care. Participants rated the Geriatric Depression Scale‐Short Form positively. The survey also provided information on how screening could be conducted in primary care settings to maximize OAs' comfort. Participants preferred screening in the waiting room or examination room instead of the nurse's station. Those receiving the pamphlet became significantly more willing to be screened for depression than those who did not, F (1, 134) = 4.47, p = 0.04. Conclusion: Most OAs appear receptive to completing a depression screen in primary care settings. Educating OAs about the value of depression screening and tailoring recognition systems to account for preferences may be an initial step in improving recognition rates. Copyright © 2017 John Wiley & Sons, Ltd.